ASAS LEGALITAS DAN TREN PENINGKATAN KEJAHATAN SIBER DI INDONESIA: KAJIAN HUKUM EMPIRIS BERBASIS STATISTIK DESKRIPTIF - Candra niko; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of information technology constantly introduces new cybercrime modi operandi, challenging the boundaries and implementation of the legality principle in Indonesian criminal law. This study aims to map the characteristics of rising cybercrime trends and critically analyze the limitations of the legality principle in addressing these developments. The research employs an empirical legal method with a sociological jurisprudence approach. Descriptive statistical analysis is applied to the statistical recapitulation of public reports throughout 2025, accessed via the Cyber Crime Investigation Portal of the Indonesian National Police (Polri) on June 20, 2026. The findings indicate a significant upward trend in cybercrime reports, with online fraud emerging as the most reported category (39.9%), followed by cyber-extortion/threats (23.7%), and online defamation (18.1%). The legal implications of these data trends show that rigid adherence to the principles of lex scripta, lex certa, and lex stricta within the formal legality framework potentially risks creating a legal vacuum or statutory limitations when facing fast-paced technological shifts. This study suggests a necessary reorientation of the legislative formulations toward a more adaptive approach while firmly upholding the fundamental principle of legal certainty.